2015
DOI: 10.1007/s00299-015-1830-9
|View full text |Cite
|
Sign up to set email alerts
|

Selection of reference genes for quantitative real-time PCR normalization in creeping bentgrass involved in four abiotic stresses

Abstract: This study identified stable reference genes for normalization of gene expression data in qRT-PCR analysis of leaf and root tissues in creeping bentgrass under four abiotic stresses. Examination of gene expression using quantitative real-time PCR (qRT-PCR) in plant responses to abiotic stresses can provide valuable information for stress-tolerance improvement. Selecting stable reference genes for qRT-PCR analysis is critically important. The objective of this study was to determine the stability of expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 36 publications
5
55
0
Order By: Relevance
“…Moreover, high stability levels were observed using geNorm analysis; all the M values were below the accepted threshold of 1.5 (Fig 2), which indicated that all the genes could be used as internal control genes for normalization. However, according to different algorithms and analytical procedures, several differences were observed in the ranking of the most stable genes, which was similar to the results for other species [1921]. For wounding treatment in S .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, high stability levels were observed using geNorm analysis; all the M values were below the accepted threshold of 1.5 (Fig 2), which indicated that all the genes could be used as internal control genes for normalization. However, according to different algorithms and analytical procedures, several differences were observed in the ranking of the most stable genes, which was similar to the results for other species [1921]. For wounding treatment in S .…”
Section: Discussionsupporting
confidence: 78%
“…Traditional reference genes, such as ACT , GAPDH , and EF1α , which are involved in primary metabolism or other cellular processes [19], as well as new candidate reference genes derived from public databases [12, 17, 22, 25, 26], have been validated to allow precise interpretation of the qRT-PCR results for specific experimental conditions. However, fluctuating expression of reference genes has been observed under certain experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PP2A expressed stably in Pennisetum glaucum under different abiotic stresses and hormonal stimuli (Saha and Blumwald, 2014; Shivhare and Lata, 2016), Caragana intermedia under osmotic and heat stress (Zhu et al, 2013), Agrostis stolonifera under different abiotic stresses (Chen et al, 2015), Brassica napus under drought, salinity and JA stresses (Wang et al, 2014b), Cynodon dactylon under different abiotic stresses (Chen et al, 2014). ACT7 , one of the best reference genes in this study, was also stably expressed under different abiotic stresses and hormonal stimuli of Daucus carota (Tian et al, 2015), JA and ABA stresses of Brassica napus (Wang et al, 2014b), drought stress of Populus euphratica (Wang et al, 2014a), and Agrostis stolonifera (Chen et al, 2015). Another stable gene is PTB , a novel reference gene identified in A. thaliana , has been identified as one of the best reference for Gossypium hirsutum (Artico et al, 2010) under abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to validate the stability of the reference gene under determined experimental condition to ensure proper normalization and a robust RT-qPCR analysis14. Several studies have been published with the aim of identifying suitable reference genes for expression analysis under different stages of the plant life cycle15161718 or under biotic and abiotic stresses19202122.…”
mentioning
confidence: 99%